Are CEOs Rewarded for Luck? The Ones Without Principals Are - Bertrand, M.; Mullainathan, S. (Quarterly Journal of Economics, 2001)
The contracting view of CEO pay assumes that pay is used by shareholders to solve an agency problem. Simple models of the contracting view predict that pay should not be tied to luck, where luck is defined as observable shocks to performance beyond the CEO's control. Using several measures of luck, we find that CEO pay in fact responds as much to a lucky dollar as to a general dollar. A skimming model, where the CEO has captured the pay-setting process, is consistent with this fact. Because some complications to the contracting view could also generate pay for luck, we test for skimming directly by examining the effect of governance. Consistent with skimming, we find that better governed firms pay their CEO less for luck.